2005
DOI: 10.1542/peds.2004-1510
|View full text |Cite
|
Sign up to set email alerts
|

Physician Reimbursement Levels and Adherence to American Academy of Pediatrics Well-Visit and Immunization Recommendations

Abstract: Immunization and well-visit rates for infants, children, and adolescents were positively linked with physician reimbursement rates for those services. Although methodologic limitations suggest caution when interpreting these findings, more attention should be given to physician reimbursement levels as a possible predictor of immunization and well-visit rates as measures of quality of care and to the importance of reimbursement levels for pediatrician recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…The rate of preventive health care visits, as determined on the basis of diagnostic and procedure codes in health care databases (eg, International Classification of Diseases, Ninth Revision, codes) rather than adolescent or parent reports, was lower. 42 According to 2002 Health Plan Employer Data and Information Set (HEDIS) data, 34% of US adolescents made 1 or more preventive health care visits during the study year. 42 The extent to which the difference in rates of preventive health care visits between HEDIS and selfreported adolescent and parent data that reflect undercoding of preventive visits versus adolescent/parent overreporting is not clear.…”
Section: Adolescent Health Care Visits and Cps Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of preventive health care visits, as determined on the basis of diagnostic and procedure codes in health care databases (eg, International Classification of Diseases, Ninth Revision, codes) rather than adolescent or parent reports, was lower. 42 According to 2002 Health Plan Employer Data and Information Set (HEDIS) data, 34% of US adolescents made 1 or more preventive health care visits during the study year. 42 The extent to which the difference in rates of preventive health care visits between HEDIS and selfreported adolescent and parent data that reflect undercoding of preventive visits versus adolescent/parent overreporting is not clear.…”
Section: Adolescent Health Care Visits and Cps Deliverymentioning
confidence: 99%
“…42 According to 2002 Health Plan Employer Data and Information Set (HEDIS) data, 34% of US adolescents made 1 or more preventive health care visits during the study year. 42 The extent to which the difference in rates of preventive health care visits between HEDIS and selfreported adolescent and parent data that reflect undercoding of preventive visits versus adolescent/parent overreporting is not clear. Despite the observation that adolescents are more likely to receive CPSs during preventive care visits, rather than acute-care visits, national and state-based surveys of adolescents and providers have shown that adolescents frequently do not receive recommended CPSs during either type of visit.…”
Section: Adolescent Health Care Visits and Cps Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Public programs often reimburse physicians and dentists at lower rates than commercial insurers (Berman et al 2002;Zuckerman et al 2004), and other payment issues (such as delays in reimbursement) may make providers less willing to provide services to children covered under these programs (Cunningham and O'Malley 2009). The literature suggests that higher Medicaid reimbursement rates can increase receipt of preventive care but that such an effect is not assured (Mayer et al 2000;Hughes et al 2005;McInerny, Cull, and Yudkowsky 2005;Shen and Zuckerman 2005).…”
mentioning
confidence: 99%
“…Attention should be paid to physician reimbursement as a predictor of the quality of care that children and adolescents receive. 4 By including the precepts of primary care in the delivery of services, managed care can be instrumental in increasing access to a full range of health care services and clinicians within a medical home. It is imperative that managed care plans fully support the intent and desired outcomes of a medical home.…”
Section: Introductionmentioning
confidence: 99%